Professionalism, Leadership Style, Understanding of Governance and Role of Supervision in Affecting Auditor Performance - Kautsar Riza Salman; Devi Saidul Hatta (JAFFA, 2020)
Auditors’ performance in general is the result of an objective audit assignment towards the financial statements of a company or other organization in order to determine whether the financial statements have been fairly presented in accordance with generally accepted accounting principles. This study aims to determine the effect of professionalism, leadership style, understanding of governance, and the role of supervision of auditor performance. This study uses a questionnaire filled out by BPKP government auditors in East Java Province. Data analysis from this study uses multiple linear regression test using SPSS 23 program. This study found that only professionalism influences auditor performance. This result implies the importance of professionalism of the auditors because it can affect performance. The results of the study also imply that external factors such as leadership style, understanding of governance, and the role of supervision are not important factors in influencing auditor performance.